Cultura vertebral Av. Calle 72 (2021)
The urban project is located in the city of Bogotá D.C Colombia, on Calle 72 con AV. Caracas in the Northeast of the capital, a sector where, through analysis, it is sought to generate an urban intervention, seeking to develop a model of strategic operations that seek to develop solutions to problems in the sector, such as the fragmentation of uses in the eastern direction - West and the discontinuity of uses that is reflected in its morphology, in the change of buildings, uses and heights, which radically change from north to south.